An evaluation of the performance diagnostic checklist–human services to assess an employee performance problem in a center‐based autism treatment facility. Issue 1 (14th October 2014) - Ditzian, Kyle; Wilder, David A.; King, Allison; Tanz, Jeanine
<x xml:space="preserve">Abstract</x> The Performance Diagnostic Checklist–Human Services (PDC‐HS) is an informant‐based tool designed to assess the environmental variables that contribute to poor employee performance in human services settings. We administered the PDC‐HS to 3 supervisors to assess the variables that contributed to poor performance by 4 staff members when securing clients in therapy rooms at a treatment center for children with autism. The PDC‐HS identified a lack of appropriate consequences as contributing to poor staff performance. We then evaluated a PDC‐HS‐indicated intervention as well as an intervention not suggested by PDC‐HS results. The PDC‐HS‐indicated intervention (graphed feedback) was effective to increase performance; the non‐PDC‐HS‐based intervention was ineffective.